2021
DOI: 10.1088/1755-1315/710/1/012014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization in one-dimensional compression of a Danish Paleogene Clay

Abstract: The North Sea Basin is characterized by the presence of highly plastic, stiff Paleogene clays sedimented between 65.5 and 43 millions of years ago. During the Quaternary Period, this area underwent a series of cyclic glaciations that overconsolidated the underneath clay deposits and sheared the shallower layers. Different studies focusing on these superficial, folded strata are present in literature. On the other hand, less information are available regarding the mechanical behaviour of the deeper, intact laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Figure 9 shows that C sp increases with σ' v-max for both SM2 and SM3 tests, as well as the intrinsic references by Di Remigio et al (2021). The SM2 tests form two groups, one for the outliers in Figure 3 and 4, which lies very close to the intrinsic trend and one for the regular tests, which positions below it.…”
Section: Swelling Phasesmentioning
confidence: 64%
See 2 more Smart Citations
“…Figure 9 shows that C sp increases with σ' v-max for both SM2 and SM3 tests, as well as the intrinsic references by Di Remigio et al (2021). The SM2 tests form two groups, one for the outliers in Figure 3 and 4, which lies very close to the intrinsic trend and one for the regular tests, which positions below it.…”
Section: Swelling Phasesmentioning
confidence: 64%
“…Figure 4 is divided into subfigures based on these swelling modes, showing for each of them; the normalised unloading branch (4a 1 , 4b 1 and 4c 1 ) and the development of C s with UI (4a 2 , 4b 2 and 4c 2 ). For comparison to the intrinsic state, the two intrinsic swelling lines (starting from 2 MPa) performed in this study, as well as an intrinsic swelling line (starting from 7 MPa) reported by Di Remigio et al (2021), are also shown in Figure 4. Figure 4a 1 and 4a 2 show the SM1 tests, which display a continuous increase of C s (positive curvature) throughout the entire unloading branch.…”
Section: Swelling Modesmentioning
confidence: 89%
See 1 more Smart Citation